2018
DOI: 10.1002/adhm.201701338
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Blood Vessels with an Oxygen Generating Composite

Abstract: Damage caused by oxygen deficiency (hypoxia) is one of the major factors limiting tissue and organ preservation time. Cooling tissues slows down metabolic rate of cells thereby prolonging tissue and organ survival sufficiently to allow transport and transplantation within a few hours. Although metabolism is slowed, cells and some enzymes continue to consume oxygen that can render cold stored tissues hypoxic. Here, an oxygen‐generating composite (OGC) with sustained oxygen release is reported for ex vivo blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Here, we selected PGS/PCL blend for entrapping CP, which shows a sustainable degradation rate and moderate hydrophilicity. Moreover chloroform-ethanol solvent had no adverse effects on the stability of CP during mixing prior to electrospinning [48].…”
Section: Discussionmentioning
confidence: 95%
“…Here, we selected PGS/PCL blend for entrapping CP, which shows a sustainable degradation rate and moderate hydrophilicity. Moreover chloroform-ethanol solvent had no adverse effects on the stability of CP during mixing prior to electrospinning [48].…”
Section: Discussionmentioning
confidence: 95%
“…Barralet and colleagues used CPO-and MnO 2 -based OGBs to sustain oxygen metabolism during organ preservation time, which is currently limited to several hours only. The study showed an increase in cell survival in aorta explants after 3 weeks with 96 ± 3% of cells surviving when OGB were used compared with 9 ± 6% when conventional vascular preservation media was used [70].…”
Section: Trends In Biotechnologymentioning
confidence: 93%
“…However, it was reported that the wall of the grafts was more prone to pseudoaneurysm and it has little longitudinal elasticity, thus restricting seeding of endothelial cells [6,7]. Therefore, the aim of this study was to develop artificial vascular grafts with structures similar to native blood vessels with the final goal of achieving regenerative medicine and organ reconstruction standards [8,9].…”
Section: Introductionmentioning
confidence: 99%